Enjoyment and intentionality in early childhood education - Nic Dunham; Andrea Delaune (New Zealand Journal of Teachers' Work)
This paper explores teacher enjoyment and the notion of the intentional teacher in early childhood education. The research is part of a wider interrogation challenging existing discourses associated with the intentional teacher. A mixed-method research design was used to gather perspectives from early childhood teachers in relation to their experiences of enjoyment in their teaching practices and the connection with being an intentional teacher. Findings from participant responses highlight important aspects associated with early childhood teacher enjoyment and intentionality. The connection between enjoyment and intentional teaching was reflected in reports of ways of doing or acting, as well as in ways of being associated with teacher identity. Connection was made between experiences of enjoyment and intentional teaching through contributing, adding value, and personal impact. Association was also made with promoting social justice. Whilst small in scale, the research highlights the importance of challenging existing and potentially limiting discourses of the intentional teacher by giving attention to how intentional teaching is generated, as an internal encounter associated with ways of being and becoming and the role that enjoyment plays within this process.